2017
DOI: 10.3390/computers6010007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Efficiency of Prompts Based on Learner Characteristics

Abstract: Abstract:Personalized prompting research has shown the significant learning benefit of prompting. The current paper outlines and examines a personalized prompting approach aimed at eliminating performance differences on the basis of a number of learner characteristics (capturing learning strategies and traits). The learner characteristics of interest were the need for cognition, work effort, computer self-efficacy, the use of surface learning, and the learner's confidence in their learning. The approach was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
1
Order By: Relevance
“…In addition to strategy questionnaires (e.g., Schwonke et al, 2006), fine‐tuning prompts based on students' online learning behaviours is another means to provide personalized support. For example, when individual students only read lecture slides, they were prompted to take self‐tests, or read supplemental materials (e.g., Backhaus et al, 2017). As evident in the study of Azevedo et al (2004), prompting students to perform metacognitive activities on the basis of their current progress improved strategy use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to strategy questionnaires (e.g., Schwonke et al, 2006), fine‐tuning prompts based on students' online learning behaviours is another means to provide personalized support. For example, when individual students only read lecture slides, they were prompted to take self‐tests, or read supplemental materials (e.g., Backhaus et al, 2017). As evident in the study of Azevedo et al (2004), prompting students to perform metacognitive activities on the basis of their current progress improved strategy use.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on various behavioural reinforcement practices and their effectiveness exists. For example, in Turkey, Backhaus, Jeske, Poinstingl and Koenig ( 2017 ) established that use of antecedent prompts was effective in transferring skills taught to young females. Similarly, Wong et al’s ( 2016 ) study in the United States of America showed that the teachers’ conceptions of ‘Nature of Science’ improved significantly after two semesters of instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Readability indices: These measures of complexity can be readily generated for texts in different languages -and have also been successfully used to construct online modules [2], assess competence [12] and support language learning [10]. New approaches also assess semantic relations inside texts (e.g., by computing the algebraic complexity of text, see [9]).…”
Section: Main Definitionsmentioning
confidence: 99%